A rare but serious complication of ticagrelor therapy: a case report. Issue 5 (20th August 2020) - Arioti, Manfredi; Sirianni, Giovanni; Laudisa, Maria Luisa; De Cesare, Nicoletta Bianca
Abstract: Background: Ticagrelor is a widely used P2Y12 inhibitor and represents a fundamental therapeutic agent in acute coronary syndrome treatment and selected post-percutaneous coronary intervention (PCI) cases. Dyspnoea and bradycardia are the most common side effects but the latter has been reported to be of trivial clinical significance Case summary: A 51-year-old gentleman underwent PCI to left anterior descending and obtuse marginal for unstable angina receiving a loading dose of ticagrelor (180 mg). During hospital stay, whilst on telemetry monitoring, a 16 s long, symptomatic, asystolic ventricular standstill was recorded prompting ticagrelor interruption and a switch to prasugrel. Discussion: Despite ventricular pauses have been reported in dedicated analyses of Phase III trials, no apparent clinical consequences were documented. However, several reports have shown that significant brady-arrhythmic events might be linked to ticagrelor administration presenting both as sino-atrial and atrio-ventricular conduction disturbances. We report a case of asystole occurring 36 h after the administration of a loading dose.